Are anticoagulants still indicated in pulmonary arterial hypertension?. (October 2018) - Olschewski, Horst; Rich, Stuart
Pulmonary arterial hypertension (PAH) is a type of pulmonary hypertension that is a progressive, fatal disease. Multiple underlying mechanisms for PAH have been identified, including vasoconstriction, intimal proliferation, medial hypertrophy, inflammation, mitochondrial dysfunction, and in situ thrombosis. Because it is an uncommon disease, it has been challenging to identify a specific treatment that targets the dominant disease mechanism in a given patient. Early success demonstrating that some patients (approximately 10%) possess pulmonary vasoreactivity at diagnosis has driven the development of pulmonary vasodilators as the mainstay of treatment. However, while they improve exercise tolerance in clinical trials, their effect on survival is limited. Therapies that target underlying disease mechanisms that affect a majority of patients are clearly needed if we are to significantly improve overall survival. In the actual guidelines, chronic anticoagulation is no longer recommended in patients with idiopathic, hereditary, and drug-induced PAH although there is much indirect evidence for this. There are data from over 40 years which include: (1) pathology studies showing the presence of thrombotic lesions in a majority of patients with PAH, both idiopathic and associated with many other conditions; (2) a similar frequency of thrombotic lesions in patients treated with pulmonary vasodilators as was seen in the years before their use; (3) mechanistic studies showing that procoagulant conditions predispose to the development of intraluminal thrombosis that contributes to vascular remodeling and the progressive nature of the pathologic changes; and (4) observational studies that, with one exception, have demonstrated a substantial survival advantage in patients with PAH treated with oral anticoagulation. Acknowledging that no prospective randomized trial with anticoagulants has ever been done, we recommend a pragmatic approach to the use of anticoagulants in PAH. We suggest that the risks and benefits of chronic anticoagulation be considered in individual patients, and that warfarin be prescribed in patients with PAH, unless they have an increased risk of bleeding. The question of whether direct oral anticoagulants (DOACs) would provide the same benefit as vitamin K antagonists is valid, but presently there are no data at all regarding their use in PAH. However, in patients with PAH in whom warfarin anticoagulation management proves problematic, it is reasonable to switch the patient to a DOAC as is current practice for other conditions.